The distribution of lead concentrations and isotope compositions in the eastern Tropical Atlantic Ocean - Bridgestock,L; Rehkamper,M; van,de Flierdt T; Paul,M; Milne,A; Lohan,MC; Achterberg,EP (Geochimica et Cosmochimica Acta, 2018)
Anthropogenic emissions have dominated marine Pb sources during the past century. Here we present Pb concentrations and isotope compositions for ocean depth profiles collected in the eastern Tropical Atlantic Ocean (GEOTRACES section GA06), to trace the transfer of anthropogenic Pb into the ocean interior. Variations in Pb concentration and isotope composition were associated with changes in hydrography. Water masses ventilated in the southern hemisphere generally featured lower 206Pb/207Pb and 208Pb/207Pb ratios than those ventilated in the northern hemisphere, in accordance with Pb isotope data of historic anthropogenic Pb emissions. The distributions of Pb concentrations and isotope compositions in northern sourced waters were consistent with differences in their ventilation timescales. For example, a Pb concentration maximum at intermediate depth (600–900m, 35pmolkg−1) in waters sourced from the Irminger/Labrador Seas, is associated with Pb isotope compositions (206Pb/207Pb=1.1818–1.1824, 208Pb/207Pb=2.4472–2.4483) indicative of northern hemispheric emissions during the 1950s and 1960s close to peak leaded petrol usage, and a transit time of ∼50–60years. In contrast, North Atlantic Deep Water (2000–4000m water depth) featured lower Pb concentrations and isotope compositions (206Pb/207Pb=1.1762–1.184, 208Pb/207Pb=2.4482–2.4545) indicative of northern hemispheric emissions during the 1910s and 1930s and a transit time of ∼80–100years. This supports the notion that transient anthropogenic Pb inputs are predominantly transferred into the ocean interior by water mass transport. However, the interpretation of Pb concentration and isotope composition distributions in terms of ventilation timescales and pathways is complicated by (1) the chemical reactivity of Pb in the ocean, and (2) mixing of waters ventilated during different time periods. The complex effects of water mass mixing on Pb distri